Zerwanie konkordatu z dnia 10 lutego 1925 roku przez Tymczasowy Rząd Jedności Narodowej - wybrane aspekty - Konrad Zurek (Studia Paradyskie)
The regaining of independence by the Polish state in 1918, at the very beginning, raised many problems of political and legal nature, which needed to be settled immediately. On February 10th, 1925, Poland and the Holy See signed a concordat that led to many political and legal changes in the country, which are scrutinised in the study. The paper discusses a legal matter and circumstances connected with ceasing of the concordat by Provisional Government of National Unity. Legal acts and extensive literature on the subject are adopted in the study. The position of both parties involved in the dispute is also presented. This article is dedicated to researchers of the relations between the State and the Catholic Church, as well as to all those who would like to deepen their legal and historical knowledge.